A Novel Nanobody Directed against Ovine Myostatin to Enhance Muscle Growth in Mouse - Kepeng Ou; Youjian Li; Peng Wu; Jixing Guo; Xiujing Hao; Jinliang Sheng; Chuangfu Chen (Animals, 2020)
Myostatin (MSTN) is a member of the transforming growth factor beta superfamily and is a negative regulator of myogenesis. It has been shown to function by controlling the proliferation of myoblasts. MSTN inhibition is considered as a promising treatment for promoting animal growth in livestock. Nanobodies, a special antibody discovered in camel, have arisen as an alternative to conventional antibodies and have shown great potential when used as tools in different biotechnology fields, such as diagnostics and therapy. In this study, we examined the effect of MSTN inhibition by RMN on the muscle growth of mice. The results showed that RMN could specifically detect and bind MSTN, as well as inhibit MSTN activity. A significant increase in skeletal muscle mass was observed after intramuscular injection of RMN into mice. Enhanced muscle growth occurred because of myofiber hypertrophy. These results offer a promising approach to enhance muscle growth that warrants further investigation in domestic animals.